The Anxiety Level of Mother Presectio Caesar with Benson’s Relaxation Therapy - Jek Amidos Pardede; Irvandy Tarigan (Poltekkes Kemenkes Semarang, 2020)
Background: Sectio caesar is a surgical action to remove a baby from the uterus by an incision in the mother's abdominal wall that aims to save the mother and baby so that the mother can deliver the baby in a healthy condition and can be born safely. Sectio Caesar often makes the mother experience anxiety that affects physical conditions that can interfere with the process of the cesarean section, so it requires the treatment of Benson in dealing with anxiety.Purpose: Analyse differences between before and after Benson’s relaxation therapy on pre-sectional Cesarean anxiety level.Methods: The study used the Quasy experiment One Group pre and Post-test design to. The technique of taking samples using purposive sampling and the number of samples wee 14 respondents. Data collection used a questionnaire. Data analising used McNemar test with a significance of 95% and p 0.05.Results: The anxiety level of pre-cesarean section mothers before was 78.6% and after Benson therapy was 85.7% with a p-value 0.004 ( 0.05).Conclusion: The Benson’s relaxation therapy is working on pre-section cesarean mothers by decreassing mothers’ anxiety levels.